# Can you please give me one of them so I cansolve for the other one?PLease!

The general formula for a straight line is y = mx + b.
Just plug the points into the equation to arrive at two equations.
6=2m+b
10=4m+b
you have two equations and two unknowns. Solve them simultaneously to obtain an answer for b

Multiply the first equation by -2. Leave the other one as is.
-12=-4m-2b
10=4m+b
=============
-2 = 0m -b or
-2 = -b
and b = 2
Check my arithmetic. Now plug b into one of the equations to solve for m, then plug those two values into your original equation to see if it is satisfied. If so, then 2 is the answer you need.

It would be helpful, and get you quicker answers, if you put the SUBJECT (in this case math) in the SUBJECT line.

Thanks.

=)

What would be the missing piece of information given the following information:

Find the equation of the line that passes through the points (2, 6) and (4, 10).

y = 2x + ?

4

2

7

5

The general formula for a straight line is y = mx + b.
Just plug the points into the equation to arrive at two equations.
6=2m+b
10=4m+b
you have two equations and two unknowns. Solve them simultaneously to obtain an answer for b

15 years ago

## I need help with this problem for homework

for graphing and linear equations

y=2x-4.2

8 months ago

## To find the missing piece of information for the equation of the line that passes through the points (2, 6) and (4, 10), we can use the given points to create two equations.

Let's use the formula for a straight line: y = mx + b.

1. Plug in the coordinates of the first point (2, 6):
6 = 2m + b

2. Plug in the coordinates of the second point (4, 10):
10 = 4m + b

We now have two equations with two unknowns (m and b). To solve these equations simultaneously, we can use various methods like substitution or elimination. Let's use elimination in this case.

Multiply the first equation by -2 to cancel out the m term:
-12 = -4m - 2b

Now, write the second equation as is:
10 = 4m + b

-12 + 10 = -4m - 2b + 4m + b

Simplify:
-2 = -b

To find the value of b, multiply both sides of the equation by -1:
b = 2

Now that we have found the value for b, we can substitute it back into one of the equations to solve for m. Let's use the first equation:

6 = 2m + 2
Subtract 2 from both sides:
4 = 2m
Divide both sides by 2:
m = 2

Therefore, the equation of the line that passes through the points (2, 6) and (4, 10) is y = 2x + 2.

To double-check, substitute the values of m and b into the original equation (y = mx + b):
y = 2x + 2
6 = 2(2) + 2
6 = 4 + 2
6 = 6

The equation is satisfied, so the missing piece of information is b = 2.